KombinasiTepungKacangHijau dan Buah Nanas dalamPembuatanSnack Bars - Dian Eva; Noviar Harun; Yusmarini Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was get appropriated combination of mung bean flour and pineapple and the sensory properties snack bars with the best quality.This research used Completely Randomized Design method with five treatments and three replications. The treatments in this research were KN1 (75% mung bean flour and 25% dried pineapple), KN2 (70% mung bean flour and 30% dried pineapple), KN3 (65% mung bean flour and 35% dried pineapple), KN4 (60% mung bean flour and 40% dried pineapple), KN5 (55% mung bean flour and 45% dried pineapple). The data obtained was analyzed statistically by using ANOVA and DNMRT at 5% level. Results of the research showed that the combination of mung bean flour with dried pineapple significantly effected on the parameters observed. The best treatment from the research was KN3 (65% mung bean flour and 35% dried pineapple) which had 16.39% water content, 1.73% ash content, 55.35% carbohydrate content, 12.31% fat content, 14.22% protein content, and 2.54% crude fiber content. Overall to result of sensory test preferred by the panelists with descriptions of brown colour, slightly mung bean and pineapple flavor, mung bean and pineapple taste, solid and slightly tender texture. Keyword :Mung bean flour, pineapple, snack bars.